MEREDUKSI BAYANGAN PADA OBYEK FOTOGRAFI MELALUI REKAYASA PENCAHAYAAN KOMPAK - Setyo Tohari Catyuriyanto (Texture: Visual Art and Culture Journal, 2023)
This research focuses on lighting techniques that reduce shadows resulting from lighting effects. This is done by arranging the lighting in a circular manner outside of the camera lens, so that the angle of the light hitting the object results in the shadow of the lamp is invisible through the lens as it is hidden behind the object. The lighting engineering is made to resemble a ringflash using an L.E.D light source available at any electrical store, making it easier for anyone who wants to make one. The advantage of this lighting engineering is the significant cost savings because ring flashes available in the photography market with certain brands are worth hundreds of millions of rupiah. This lighting engineering is made larger with a diameter of 50 centimetres and is flexible so that it can be used dynamically for fashion, product and other shoots. The achievement of this research is a compact lighting prototype, this research also presents a guide to making lighting engineering so that it can be used by photo studio creative industry players in improvingshooting results